Macro Adjustment Policies and Horizontal Inequalities. - Langer, A; Stewart, F (CRISE (Department of International Development, University of Oxford), 2008)
While there has been a considerable amount of analysis on the impact of structural adjustment policies on poverty and inequality among individuals (or what we define here as vertical inequality – VI), there has been almost none into the impact of structural adjustment on inequality between culturally defined groups, or horizontal inequality (HI). Although relatively neglected in economic analysis, socioeconomic HIs are important from a number of perspectives – they can have adverse effects on the wellbeing of members of the deprived groups, they can impede efficiency, they may make it very difficult to eradicate poverty, they lead to unfair and exclusionary societies, and they raise the risk of violent conflict. Hence it is important to analyse the impact of structural adjustment policies on HIs – which is the aim of this paper.